The pains of life imprisonment during late adolescence and emerging adulthood - Wright, Serena (The Palgrave international handbook of youth imprisonment, 2021)
In recent years, the prison estate of England and Wales has received into custody a growing number of life-sentenced prisoners serving very long minimum terms, many of whom were convicted at a young age. This chapter draws on a substratum of data generated by a large mixed-methods study examining the experience of serving a long life sentence in England and Wales from the point of late adolescence and early adulthood. Focusing chiefly on qualitative data from interviews with incarcerated men and women aged 18 to 25 years, we conclude that the pains of long-term imprisonment among this group coalesce around losses in three key areas: relational, temporal, and the deprivation of stimulation (broadly conceived). We explore the nature, experience, and impact of these losses among young life-sentenced prisoners, concluding that whilst relational pains represent an equaliser across generational gaps in the long-term prisoner population, the temporal and deprivation-centered challenges of a life sentence—particularly in the initial years—interact in a uniquely painful way with young age.